PENINGKATAN KINERJA PEGAWAI NEGERI SIPIL SEBAGAI IMPLIKASI UNDANG-UNDANG NOMOR 5 TENTANG APARATUR SIPIL NEGARA DI KANTOR KECAMATAN MALUNDA - Jamaluddin Jamaluddin; Andriani Andriani (MITZAL (Demokrasi, Komunikasi dan Budaya) : Jurnal Ilmu Pemerintahan dan Ilmu Komunikasi, 2018)
This study aims to determine the Improvement of the Performance of Civil Servants as the implication of Law Number 5 concerning the State Civil Apparatus in the Malunda District Office. The study used descriptive qualitative methods to make a description of facts, certain characteristics systematically, factually, and accurately. The results of the study show that the level of work discipline of the State Civil Apparatus employees at the Malunda Sub-District Office is still far from the standard. Factors that influence performance and performance improvement in carrying out services are internal motivation, employee knowledge, and employee welfare.